Legitimacy in mind: Internal deliberations and judgment formation - Danny Buckley; Natalia Vershinina (2025)
Our study seeks to contribute to the field of legitimacy theory by developing a micro-level understanding of the dynamics of legitimacy judgment formation and change. To achieve this aim, we ask the overarching research question: How do individuals' internal conversations influence their justification and legitimisation of actions within structurally constrained contexts?